Pedagogical interpretation of information about biomechanical characteristics of sprinting among female athletes - Meshcheryakov, A. V. (The Russian Journal of Physical Education and Sport, 2018)
In terms of general theses, characterizing rational forms of the training process organization an athlete`s individuality can be reflected. Methodical rules, which show the essence and the limits of training lessons individualization among qualified athletes, are very urgent. Biomechanical peculiarities reflection of the inner content of movements can be successfully used for pedagogical estimation of an athlete`s motor activity state and its development management in the training process. Materials. The article offers a pedagogical interpretation of the information about biomechanical characteristics of sprinting among female athletes of different qualification. Research methods. scientific-methodical literature analysis, sprinting trainers` progressive pedagogical experience summarizing, pedagogical experiment, testing, statistical data handling. Results. A new approach to the training and competitive activity of highly-qualified female track and field athletes is offered. A pedagogical interpretation of the information about biomechanical characteristics of different qualification female sprinters is given. The experimental methodology is created, based on the complex of individual-technical and personal peculiarities of female athletes, which condition competitive activity success. The research results confirmed the hypothesis about qualitative differences in starting stride rhythm as the system of regulated equalities of biochemical characteristics. Two kinds of starting stride rhythm are revealed. The held analysis gave an opportunity to define three main groups of runners with different leading component during 100 meters distance overcoming. The received results about the character of efforts during the supporting reactions, indirectly indicate power potential, can help to define the type of dynamic structure and plan the program of its development. Conclusion. The results of the pedagogical experiment showed the expediency and effectiveness of biomechanical approach use the running technique estimation, which helped to improve competitive activity indices among qualified female athletes.